2017
DOI: 10.1177/2309499017727920
|View full text |Cite
|
Sign up to set email alerts
|

Is calcar referenced tip-apex distance a better predicting factor for cutting out in biaxial cephalomedullary nails than tip-apex distance?

Abstract: Purpose: To test the significance of calcar referenced tip-apex distance (CalTAD) and the length of anti-rotation screw (AR screw) as predictors for failure after biaxial cephalomedullary (CM) nailing of intertrochanteric fractures. Methods: We retrospectively reviewed 190 consecutive fractures that had undergone biaxial CM nailing. Of these, 67 met the inclusion criteria of a non-pathological fracture with a minimum of 90 days radiological follow-up (mean 458 days; 91 days to 4.9 years). Results: The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Mean TAD total was 22.8mm while TAD ap and TAD lateral was 11.8 and 11.0mm respectively ( Table IV ). TAD has been poorly studied in biaxial cephalomedullary implants (having two screws) such as ours and currently there is no proven or recommended TAD for such implants 15 , 16 . Most frequent position of lag screw was charted in inferior-central zone in 95 cases ( Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Mean TAD total was 22.8mm while TAD ap and TAD lateral was 11.8 and 11.0mm respectively ( Table IV ). TAD has been poorly studied in biaxial cephalomedullary implants (having two screws) such as ours and currently there is no proven or recommended TAD for such implants 15 , 16 . Most frequent position of lag screw was charted in inferior-central zone in 95 cases ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Baumgartner’s original description of TAD pertains with sliding hip screw system with a large single cephalic screw. It has been extrapolated and used in cephalomedullary nails including dual screw systems such as ours 15 , 16 . TAD was measured for only the lag screw as hip pin gets obscured by the lag screw in lateral view.…”
Section: Methodsmentioning
confidence: 99%
“…Jiamton et al18) reported that the risk of perforation of the femoral head was decreased when the tip of the blade was located in the inferior half of the femoral head. Kashigar et al,10) Caruso et al,15) and Puthezhath and Jayaprakash12) reported that the risk was decreased when the calTAD decreased. In addition, according to Stiehl et al,9) the inferior side of the femoral neck is a dense trabecular structure, which is more resistant to loading stress than other parts of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not investigate the clinical outcome. In previous papers, the impact of blade position on the clinical outcome was already addressed 10121518). Therefore, we focused on assessing the quality of reduction and the position of the blade radiologically in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation